Simulation for fiber-coupled diode lasers by considering discreteness in propagation angles of individual emitters. (December 2020) - Dong, Zhiyong; Zhao, Pengfei; Lin, Guyi; Lin, Xuechun
Highlights: Simulation technique for actual diode lasers with measured propagation angles. The method provides a more accurate simulation for fiber coupling of diode lasers. The technique could provide a method for selecting diode laser stacks. Abstract: It is vitally important to numerically simulate the output power spatial distribution of diode laser stacks when they are used in beam shaping and pumping for other lasers. Here, we propose a numerical simulation technique by considering the discreteness of the propagation angles of individual emitters in diode laser stacks in the fast axis. Using this proposed simulation technique, we calculated the spatial distribution of the outputs of the four diode laser stacks and the total output power of the 3000 W fiber-coupled diode laser. The calculated results agree well with the experimentally measured values. Therefore, when designing a laser, this is a useful way to select diode laser stacks based on specifications.